Growth Performance and Immune Response of Free-range Chicken Supplemented with Different Levels of Spirulina (arthrospira platensis) in their Diet - Estudillo, Sinamar E. (Future Science / FSH-PH Publications, 2022)
The study was conducted to determine the effects on the growth performance and immune response of free-range chicken supplemented with different levels of spirulina in their diet. Sixty free range chicken, fifteen day-olds, were used in the study which were randomly distributed in four treatments, three replicates in each treatment with five experimental birds in each replicate. Treatment 1- Control (pure commercial feeds); Treatment 2- 4% spirulina supplemented in commercial feeds; Treatment 3 -5% spirulina supplemented in commercial feeds and Treatment 4 – 6% spirulina supplemented in commercial feeds. Initial and final weight reveal that they are replicate significantly different among the four treatments whereas Average Daily Gain and Feed Conversion Ratio showed no significant differences among treatments, however, Treatment 4 exhibited efficiency in feed conversion and has the highest gain in weight among treatments. In hemagglutination Inhibition test, all treatments responded positive in immune response.